Emotion dysregulation and loneliness as predictors of food addiction - Eirini Tatsi; Atiya Kamal; Alistar Turvill; Regina Holler (Journal of Health and Social Sciences)
Introduction: This study aimed to investigate whether multiple aspects of emotion dysregulation contribute to the etiology of Food Addiction (FA); as well as to provide further evidence and clarity regarding the role of loneliness on the development of addictive behaviour towards food. Methods: A correlational study was employed to assess associations within 162 participants which were recruited via online forums on FA and student population. The Yale Food Addiction Scale (YFAS), Difficulties in Emotion Regulation Scale (DERS), and UCLA Loneliness Scale, and a demographic and personal information questionnaire were all completed online. A Poisson regression analysis was carried out and statistical significance was set at P <0.05. Results: 79% of the sample endorsed a persistent desire or repeated unsuccessful attempts to cut down or control their use of highly processed foods, while 21% met diagnostic criteria for food addiction. Poisson regression analysis demonstrated that the model predicts food addiction (P <0.001). Specifically, food addiction symptom count was positively predicted by difficulty engaging in goal-directed behaviour, impulse control difficulties, lack of emotional awareness and limited access to emotion regulation strategies (P <0.05); DERS total, nonacceptance of emotional responses and lack of emotional clarity were not significant predictors. Loneliness positively predicted food addiction (P =0.002). Discussion and Conclusions: The findings of this research provide further evidence on the etiology of food addiction, as multiple aspects of emotion dysregulation, including difficulty in engaging in goal-directed behaviour, impulsiveness, emotional awareness and limited access to emotion regulation strategies, and loneliness were found to influence the development of an addictive behaviour towards certain types of food. Future research will need to understand possible causality between these factors and insights into the potential role addictive behaviour of food has in overeating phenomena, such as binge-eating.